Combining a Nitrogenase Scaffold and a Synthetic Compound into an Artificial Enzyme. (16th October 2015) - Tanifuji, Kazuki; Lee, Chi Chung; Ohki, Yasuhiro; Tatsumi, Kazuyuki; Hu, Yilin; Ribbe, Markus W.
Abstract: Nitrogenase catalyzes substrate reduction at its cofactor center ([(Cit)MoFe7 S9 C] n − ; designated M‐cluster). Here, we report the formation of an artificial, nitrogenase‐mimicking enzyme upon insertion of a synthetic model complex ([Fe6 S9 (SEt)2 ] 4− ; designated Fe6 RHH ) into the catalytic component of nitrogenase (designated NifDK apo ). Two Fe6 RHH clusters were inserted into NifDK apo, rendering the conformation of the resultant protein (designated NifDK Fe ) similar to the one upon insertion of native M‐clusters. NifDK Fe can work together with the reductase component of nitrogenase to reduce C2 H2 in an ATP‐dependent reaction. It can also act as an enzyme on its own in the presence of Eu II DTPA, displaying a strong activity in C2 H2 reduction while demonstrating an ability to reduce CN − to C1 –C3 hydrocarbons in an ATP‐independent manner. The successful outcome of this work provides the proof of concept and underlying principles for continued search of novel enzymatic activities based on this approach. Abstract : Roter Teppich für Fe6 RHH : Ein negativ geladener synthetischer Modellkomplex (Fe6 RHH ), der die Topologie des Nitrogenase‐Cofaktors imitiert, kann über einen positiv geladenen Insertionspfad in die katalytische Komponente der Nitrogenase (NifDK apo ) eingeführt werden. Daraus resultiert ein künstliches Enzym, das C2 H2 ATP‐abhängig und ‐unabhängig zu C2 H4 sowie CN − ATP‐unabhängig zu C1 ‐ bis C3 ‐Kohlenwasserstoffen reduzieren kann.